Building Cross-Functional Collaboration Models Between Compliance, Risk, and Business Units in Finance - Olasunbo Olajumoke Fagbore,; Jeffrey Chidera Ogeawuchi,; Oluwatosin Ilori,; Ngozi Joan Isibor,; Azeez Odetunde,; Bolaji Iyanu Adekunle, (International Journal of Scientific Research in Science and Technology, 2024)
In today’s increasingly complex financial landscape, the alignment of compliance, risk management, and business operations has become a critical success factor for institutions navigating evolving regulatory expectations, reputational risks, and operational complexity. This study examines the development and implementation of cross-functional collaboration models between compliance, risk, and business units, drawing upon my career-wide experience coordinating across diverse teams within high-compliance financial environments. Throughout my professional journey, I have consistently facilitated structured collaboration between departments traditionally siloed by function. My contributions have focused on aligning compliance objectives with operational realities, enabling risk-informed business strategies, and establishing streamlined communication channels that ensure regulatory transparency without impeding business agility. Working within private equity, real estate funds, and investment operations, I designed and implemented integrated workflows and committee structures that brought together risk analysts, compliance officers, and business executives for real-time issue escalation, control mapping, and project execution. The proposed model emphasizes a shared governance structure that incorporates risk-based decision-making, compliance oversight, and business enablement in a unified framework. Key pillars include standardized reporting protocols, cross-functional risk assessments, compliance onboarding for business teams, and regular stakeholder engagement via governance committees. These models foster transparency, mutual accountability, and quicker resolution of regulatory, reputational, and operational risks. Evidence from implemented initiatives shows enhanced issue resolution timelines, improved audit outcomes, and greater alignment of business growth objectives with regulatory requirements. By embedding compliance and risk professionals in business planning processes, institutions have achieved stronger internal control environments, greater readiness for regulatory reviews, and reduced friction in product delivery timelines. This paper offers a practical roadmap for financial institutions to build integrated collaboration models that are scalable, sustainable, and adaptable to local and global compliance regimes. It underscores the importance of compliance culture, leadership engagement, and centralized knowledge sharing in achieving long-term organizational resilience and competitive differentiation.
Keywords: Cross-Functional Collaboration; Compliance Integration; Risk Coordination; Financial Governance; High-Compliance Environments; Operational Alignment; Business Strategy; Internal Controls; Regulatory Engagement; Stakeholder Governance